2017
DOI: 10.1039/c7sm00048k
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting oligomer/polymer compatibility and the impact on nanoscale segregation in thin films

Abstract: Compatibility between oligomers and polymers was systematically assessed using differential scanning calorimetry (DSC) and was correlated with similarity in saturation and solubility parameter. These measurements enabled validation of detailed volume of mixing calculations using Statistical Association Fluid Theory (SAFT-γ Mie) and molecular dynamics (MD) simulations, which can be used to predict behaviour beyond the experimentally accessible conditions. These simulations confirmed that squalane is somewhat mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…When it is too high, the surface segregation can be inhibited [39] or within the time scale required for our spreading experiments will be partially realized. This surface migration has been confirmed experimentally using X-ray photoemission spectroscopy [40] and neutron reflectivity [41]. Since the molecular size of PDMS5 is much smaller than the one of PDMS500, we do expect such segregation at the liquid/air interface.…”
Section: Comparison Of the Two-regimes Transition Between Pure And Mixture Pdmssupporting
confidence: 57%
See 1 more Smart Citation
“…When it is too high, the surface segregation can be inhibited [39] or within the time scale required for our spreading experiments will be partially realized. This surface migration has been confirmed experimentally using X-ray photoemission spectroscopy [40] and neutron reflectivity [41]. Since the molecular size of PDMS5 is much smaller than the one of PDMS500, we do expect such segregation at the liquid/air interface.…”
Section: Comparison Of the Two-regimes Transition Between Pure And Mixture Pdmssupporting
confidence: 57%
“…Two plausible mechanisms are proposed to account for them. When a homogenous polymer mixture having different mobile components is exposed to air, it has been confirmed that the smaller molecule component migrates to the free surface [38][39][40][41], if the concentration of big molecules is not too high. When it is too high, the surface segregation can be inhibited [39] or within the time scale required for our spreading experiments will be partially realized.…”
Section: Comparison Of the Two-regimes Transition Between Pure And Mixture Pdmsmentioning
confidence: 98%
“…Unfortunately, for many systems the combining rules do not work as well. 107 However, simple improvements to the fitting of thermodynamic data within SAFT-γ Mie can be made by allowing the k i j parameter to vary from zero. 108 A further interesting comparison between the bottom-up and top-down approaches is the shape of the potentials they produce.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data for complex, yet well-defined systems are needed to define the influence of molecular structure on those models. For example, molecular weight (Mw) is included in basic models for compatibility such as Flory Huggins theory, but modern theories need to consider the dependence of chain flexibility, free volume, and specific interactions on mixing in order to have a useful predictive capacity [15].…”
Section: Properties Of Polymer-migrant Mixtures: Changing Migrant Conmentioning
confidence: 99%
“…Following the method described by Sabattié et al [15], samples for DSC analysis were produced by adding drops from the mixed solutions to standard DSC aluminum pans, drying each drop in an oven set to 40 • C and repeating the process until 4-6 mg of solid material had been deposited into the aluminum pan. DSC analysis of the resulting samples was run on a Perkin Elmer DSC8500 instrument using nitrogen as the purge gas at a flow rate of 20.0 mL min −1 .…”
Section: Thermal Analysismentioning
confidence: 99%